Charisma and Capitalism in Motion: the Continuing Relevance of Robert P. Weller’s Ideas for Indonesian Islamic Modernity - Roberto Arieza Martin Purba; Dody S. Truna; Rifki Rosyad (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study examines Robert P. Weller’s theoretical contributions to understanding the relationship between religious transformation and the capitalist economic system in Asia. Weller challenges the Weberian secularization paradigm by proposing a dialectical model of secularization–religionization and a typology of three religious responses to capitalism: embracing amorality, prosperity theology, and philanthropic amelioration. Through empirical studies in Taiwan, he demonstrates that religion is not a victim of modernity but a moral actor negotiating global economic values. This review evaluates Weller’s theoretical framework, methodological approach, empirical contributions, as well as its limitations and directions for future research.